2021
DOI: 10.1016/j.resinv.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Human epididymis protein 4 is a new biomarker to predict the prognosis of progressive fibrosing interstitial lung disease

Abstract: BACKGROUND The clinical course and prognosis of progressive fibrosing interstitial lung diseases (PF-ILDs) vary from individual to individual. Predictive serum biomarkers for the management of the disease are needed. Serum human epididymis protein 4 (HE4) has been reported to be elevated in patients with IPF, yet its clinical utility has not been elucidated. We evaluated whether serum HE4 could be a biomarker for patients with PF-ILD. METHODS Serum HE4 was measured in a retrospective study that consisted of 34… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
4
10
0
1
Order By: Relevance
“…Further, we found that high levels of HE4 were independently associated with the presence of RA-ILD in a multivariate logistic regression analysis. Consistent with our results, Nishiyama et al also showed that HE4 was a new biomarker to predict the prognosis of progressive fibrosing ILD (20). Taken together, these findings support a role of HE4 in risk stratification of ILD.…”
Section: Discussionsupporting
confidence: 92%
“…Further, we found that high levels of HE4 were independently associated with the presence of RA-ILD in a multivariate logistic regression analysis. Consistent with our results, Nishiyama et al also showed that HE4 was a new biomarker to predict the prognosis of progressive fibrosing ILD (20). Taken together, these findings support a role of HE4 in risk stratification of ILD.…”
Section: Discussionsupporting
confidence: 92%
“…Very recently, Zhang et al reported that serum HE4 levels were significantly increased in patients with systemic sclerosis (SSc)-ILD compared to SSc-non-ILD, which was consistent with our findings (19). Nishiyama et al also showed that HE4 was a new biomarker to predict the prognosis of progressive fibrosing interstitial lung disease (20). These findings were consistent with ours showing that HE4 was significantly associated with pulmonary involvements and renal involvements in patients with pSS.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that serum HE4 could serve as a biomarker for predicting death and prognosis in ovarian cancer, chronic heart failure patients and progressive fibrosing interstitial lung diseases. 13,16,35 Taken together, we believe that serum HE4 is a biomarker of ARDS induced by sepsis and is associated with the prognosis of sepsis.…”
Section: Discussionmentioning
confidence: 78%
“…14,18 Indeed, elevated serum HE4 concentrations were reported in a series of studies to be associated with pulmonary fibrosis, and presumably a potential biomarker for the evaluation of the diagnosis, severity and progression of pulmonary fibrosis. 17,[19][20][21] However, the concentrations of serum HE4 in ARDS patients have not yet been explored. In this study, we tested the serum HE4 levels of patients with ARDS and investigated its clinical value for the diagnosis and prognosis of ARDS.…”
Section: Introductionmentioning
confidence: 99%